1987
DOI: 10.1111/j.1570-7458.1987.tb02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal chromenes from the Asteraceae: structure‐activity relations

Abstract: Chromenes (benzopyrans), common to many genera of the Asteraceae, are lethal to the neonate variegated cutworm, Peridroma saucia Hübner, when presented on the inner walls of glass vials at concentrations of 1.0 μmol/vial or less. Closely related benzofurans, including some from the same plants, are relatively inactive at these concentrations. The most potent of seven naturally‐occurring and four derived chromenes is the well known allatocidin, precocene II, with an LD50 of 0.134 μmol/vial or 0.67 μg/cm2. A mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Mortality of the samples was evaluated after 12, 24, and 48h of exposure. Responses to treated sample versus control were converted to "percentage of mortality" [21].…”
Section: Contact Toxicity Assaymentioning
confidence: 99%
“…Mortality of the samples was evaluated after 12, 24, and 48h of exposure. Responses to treated sample versus control were converted to "percentage of mortality" [21].…”
Section: Contact Toxicity Assaymentioning
confidence: 99%
“…Compounds 1 ± 5 were isolated from flowers and leaves of Pterocaulon polystachyum collected in Colonia BenÌtez, Chaco, Argentina, at the end of the summer. Identification of the compounds was accomplished by spectroscopic methods (IR, 1 H-NMR, 13 C-NMR, and MS). Purity of coumarins was checked by HPLC in Beckman C18 and C8 columns (25 Â 1 cm i.d., 5-mm particle size), using MeOH/H 2 O mixtures as eluents [15], previous to the incorporation to the insect diets.…”
Section: Experimental Partmentioning
confidence: 99%
“…It is also plausible that these secondary metabolites do not operate individually on the target but in concert, additively or synergistically [12]. Additionally, many chromenes, structurally related to compound 7 (see below) have been reported to display insect repellent and insecticidal effects [13] [14].…”
mentioning
confidence: 98%
“…Three new benzopyrans, 6isobutyryl-5,7-dimethoxy-2,2-dimethylbenzopyran (HP1), 7-hydroxy-6-isobutyryl-5-methoxy-2,2-dimethylbenzopyran (HP2), and 5-hydroxy-6-isobutyryl-7-methoxy-2,2-dimethylbenzopyran (HP3) were isolated from the aerial parts of H. polyanthemum [5]. Benzopyrans are a group of natural products that occur in plants and have shown important biological characteristics such as antioxidant [6], insecticide [7], antifungal [8], and antimalaria [9] properties as well as in vitro antitumor activity [10]. Studies performed with benzopyrans HP1, HP2, and HP3 revealed a series of bioactivities such as monoamine oxidase inhibition (MAOI) [11] and antibacterial [12] and antitumoral [13] actions.…”
mentioning
confidence: 99%